Pelaksanaan Smart Governance di Kabupaten Ciamis - Teny Cartika; Dini Yuliani; H. Otong Husni Taufiq (Journal of Research and Development on Public Policy, 2024)
Fiscal problems often escape the attention of regions responsible for developing smart cities as part of the implementation of the 100 Smart Cities movement initiated by the central government. The Ministry of Communication and Information is the initiator of implementing the smart city program. To be able to build a smart city, what must first be done is the readiness of a local government to be able to prepare the main elements. Referring to the Ciamis Regency smart city master plan (2023), Ciamis Regency is one of the districts that implements the smart city policy. However, in implementing the smart city, the Ciamis Regency Government faces various complex problems. Therefore, this research focuses on smart governance which aims to increase the efficiency of Ciamis Regency government governance. This research uses a descriptive qualitative research methodology with data collection techniques for primary subjects in the form of interviews with several officials from the Ciamis Regency Communication and Information Service as well as secondary subjects in the form of literature, documents, reports and statutory regulations to strengthen research data.